2016
DOI: 10.7205/milmed-d-15-00264
|View full text |Cite
|
Sign up to set email alerts
|

Dismounted Blast Injuries in Patients Treated at a Role 3 Military Hospital in Afghanistan: Patterns of Injury and Mortality

Abstract: Dismounted improvised explosive devices blast injuries result in devastating multiple limb amputations and unstable pelvic fractures, which are associated with mortality after initial trauma resuscitation at a Role 3 hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 12 publications
3
18
0
7
Order By: Relevance
“…Previous studies also found explosives were the most prevalent mechanism of injury with rates of 44.1%-87.9% [3,5,7,[22][23][24]26,27,29,30,[35][36][37][38][39]. Despite a significant proportion of our subjects suffering explosive or GSW injuries, overall mortality was 4.5% which is consistent with previously published mortality rates of 1.8%-6.9% [7,22,23,40,41]. Our observed mortality rate-similar to the cited studies-does not include prehospital fatalities.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies also found explosives were the most prevalent mechanism of injury with rates of 44.1%-87.9% [3,5,7,[22][23][24]26,27,29,30,[35][36][37][38][39]. Despite a significant proportion of our subjects suffering explosive or GSW injuries, overall mortality was 4.5% which is consistent with previously published mortality rates of 1.8%-6.9% [7,22,23,40,41]. Our observed mortality rate-similar to the cited studies-does not include prehospital fatalities.…”
Section: Discussionsupporting
confidence: 91%
“…These results correspond with our hypothesis and could be attributed to younger service members being more likely to be combat service members (i.e. dismounted warfighters) that are exposed to ground-emplaced IEDs [15]. In a study about dismounted blast injuries, the median age of service members was 23 years [15].…”
Section: Discussionsupporting
confidence: 89%
“…In another U.S. study, researchers reported incidence rates of open versus closed pelvic fractures to be between 7.6% and 92.4% when analyzing 24,059 patients with unstable pelvic ring fractures, respectively, using ICD-9 Clinical Modification Codes [14]. In respect to military trauma, a U.K. Military study reported an overall incidence rate of 7.4% among dismounted soldiers admitted to a field hospital due to blast injuries sustained from IED explosions [15]. Another study using U.K. Military Joint Theatre Trauma Registry reported a total incidence of pelvic ring fractures (both open and closed) to be 0.83 per 1,000 person-years [16].…”
Section: Discussionmentioning
confidence: 99%
“…4,13,19 In the most recent wars in Afghanistan and Iraq, survivability has improved so much that despite a 64% chance of double amputation following blast injury, mortality remains as low as 1.8%. 23 However, this improvement in survivability has resulted in the greatest incidence of survivable TBI during the ongoing wars in Afghanistan and Iraq (https://dvbic.dcoe.mil/system/files/ tbi-numbers/worldwide-totals-2000-2018Q1-total_jun-21-2018_v1.0_2018-07-26_0.pdf). 8,17,22,24,33 In the current series, 41% of patients had comorbid injuries in addition to head injury requiring neurosurgical intervention, yet only 3 patients died.…”
Section: Discussionmentioning
confidence: 99%